2013
DOI: 10.1111/desc.12068
|View full text |Cite
|
Sign up to set email alerts
|

Does working memory training lead to generalized improvements in children with low working memory? A randomized controlled trial

Abstract: Children with low working memory typically make poor educational progress, and it has been speculated that difficulties in meeting the heavy working memory demands of the classroom may be a contributory factor. Intensive working memory training has been shown to boost performance on untrained memory tasks in a variety of populations. This first randomized controlled trial with low working memory children investigated whether the benefits of training extend beyond standard working memory tasks to other more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
195
5
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(232 citation statements)
references
References 39 publications
20
195
5
12
Order By: Relevance
“…Mahncke et al (2006) tested the effect through the use of two control groups and concluded that the lack of difference between the two control groups suggests that there is no meaningful placebo effect with this type of study. Dunning et al (2013) used a similar dual control group design and also concluded that experimental gains were not likely the result of expectancy effects. Burki, Ludwig, Chicherio, and Ribaupierre (2014) reported comparable results, finding no significant differences in training outcomes between active controls and no‐contact controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mahncke et al (2006) tested the effect through the use of two control groups and concluded that the lack of difference between the two control groups suggests that there is no meaningful placebo effect with this type of study. Dunning et al (2013) used a similar dual control group design and also concluded that experimental gains were not likely the result of expectancy effects. Burki, Ludwig, Chicherio, and Ribaupierre (2014) reported comparable results, finding no significant differences in training outcomes between active controls and no‐contact controls.…”
Section: Discussionmentioning
confidence: 99%
“…The modification of ‘IQ’ has been an elusive quest of many neuroplasticity researchers who have found little transfer from targeted cognitive training interventions to general intelligence (Chein & Morrison, 2010; Dunning, Holmes, & Gathercole, 2013). Although transfer from working memory training to fluid intelligence has been documented in several small studies (Jaeggi, Buschkuehl, Jonides, & Perrig, 2008; Jaušovec & Jaušovec, 2012), skepticism continues to permeate the field (Redick et al, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Comparable studies with older children have generally found that training effects, where detectable, tend to be maintained at intervals ranging from two months to a year (Dunning et al, 2013;Klingberg et al, 2005;Rueda, Rothbart, McCandliss, Saccomanno, & Posner, 2005). However, it is unknown whether training effects are as persistent in infants.…”
Section: Introductionmentioning
confidence: 99%